The Impact Of Immunisation Programmes On The Reduction Of Communicable Disease Cases In Urban Communities - Hasibuan, Ustifina Hasanah (Sean Institute, 2024)
The objective of this study is to ascertain the impact of immunisation programmes on the reduction of infectious disease cases in urban communities in East Jakarta. The research method employed was qualitative, with a case study approach. Data were collected through in-depth interviews with health workers, parents, and community leaders, as well as direct observation at several posyandu and community health centres. The results demonstrated that the immunisation programme has a substantial impact on the reduction of infectious disease cases, particularly in children, and the enhancement of public awareness regarding the significance of immunisation. Nevertheless, several challenges persist, including disparities in access to vaccination and the presence of resistance from specific community groups. The findings are anticipated to provide insights for local governments in optimising immunisation programmes in urban areas.